Habitats, population densities, and social structure of capybaras (Hydrochaeris Hydrochaeris, Rodentia) in the Pantanal, Brazil - Alho, Cleber José Rodrigues (1987)
(1) The Pantanal is the central portion of a sunken flat plain bordering the upper Paraguay river, with an area of 140,000 km 2. Seasonal floods begin in January and end in April. From May to October the land dries out and Campos (grassland formations) and scattered pools appear. (2) Typical capybara habitat in the Pantanal is composed of three components: the water, a patch of forest, and a grass field for foraging. Highest densities of capybaras (14 individuais/km2) were found during the rainy season when the avaiiable space for capybaras was reduced due to the flooding. Areas without ponds or creeks presented low densities (from 0.38 to 0.84 Capybaras/km2). Group sizes ranged from 2 to 49 individuais (~X = 9.48). (3) Reproduction occurrd year-round and young of different ages were seen throughout the year. However, the principal recruitment of young to The population was observed in july August. While the females took tums in caring for young of different ages, probably the offspring ofmothers who are sisters in the same social groups, the males competed intensively with Each other for access to breeding females. The male's reproductive success appears to be limited to the number of breeding females that males have access to in the social group.